A Time Series–Cross Section Analysis of International Variation in Crime and Punishment - Wolpin, Kenneth I. (The Review of Economics and Statistics, 1980)
T HE purpose of this paper is to ascertain the extent to which deterrence, environment, and culture can be considered responsible for the observed variance in the propensity for criminal behavior across countries. It is based on time-series observations on robberies from 1955 to 1971 for three countries: England, Japan and the United States as represented by California.1 The differential impacts on the per-capita robbery rate of the certainty and severity of punishment and of economic and demographic characteristics are estimated. Culture is defined to be the set of unmeasured crime determinants that permanently differ across countries and its effect is captured by country-specific dummy variables. The character of this unobservable is inferred from the interrelationship of country-specific effects on crime to those on punishments. The choice of the three countries is based upon the availability of fairly comparable data. We examine robbery because it is defined similarly across countries and because it combines features of both property crimes and personal crimes of violence.2 Indeed, it seems that much of the variation in crime between the United States and England is due to differences in the level of crimes with personal confrontation.3 In discussing the results, I interpret the findings as a consequence of individual maximizing behavior. There has, however, been much debate over the deterrence interpretation, a debate which cannot be resolved by any single empirical effort.4 Given the extent of the controversy, a short digression on the nature of the debate should be valuable at least in placing the present study in the appropriate context. A single equation approach, as pursued in this paper, can provide unambiguous evidence on the deterrence issue only if the level of deterrence is unaffected by variations in the level of crime. Two arguments for this feedback from crime to enforcement have been suggested in the literature, one technical and the other behavioral. The former, the congestion argument, is due to the likelihood that increased crime with fixed law enforcement resources leads to declining rates of capture, conviction, and punishment. This phenomenon is mitigated by the second mechanism which is based upon the societal response to increased crime of expanding law enforcement activity. The extent to which the technical feedback is relevant depends upon the degree to which society anticipates variations in crime and the rapidity with which adjustments in law enforcement inputs can optimally be made, i.e., on costs of adjustment. A priori, it is impossible to tell which one of these will dominate in any set of observations and, thus, impossible to ascertain the direction of the bias in deterrence estimates. Indeed, each of the several law enforcement stages (arrest, conviction, sentencing) may, through these two avenues, be differentially responsive to the crime level. Two strategies can be followed given this problem, each of which may potentially contribute to our ultimate understanding. Which one is chosen depends essentially on the availability of data. One method involves estimating the supply of crime equation within the setting of a multiple equation framework using a suitable estimation technique. Much of the debate over deterrence has been concerned, therefore, with the identification issue, and it has been argued that results which employ simultaneous equation estimaReceived for publication August 15, 1978. Revision accepted for publication November 26, 1979. * Yale University. This paper was prepared under Grant Number 75N1-99-027 from the National Institute of Law Enforcement and Criminal Justice, Law Enforcement Assistance Administration, U.S. Department of Justice. Points of view or opinions stated in this document are my own and do not necessarily represent the official position or policies of the U.S. Department of Justice. I am indebted to John Treat for performing the translations of the Japanese criminal statistics. I The data for the United States as a whole are not as complete as for California alone. 2 Robbery is basically defined as a theft with violence or the threat of violence. 3 See Wolpin (1978) for a comparison of U.S. and English property crime rates. 4 See the collection of papers in Blumstein, Cohen, and Nagin (1978) for a critical view of the deterrence framework and a lengthy discussion of alternative interpretations. [ 417 1